The gender gap in lifetime earnings: The role of parenthood - Rick Glaubitz; Astrid Harnack-Eber; Miriam Wetter (Freie Universität Berlin, School of Business & Economics, 2022)
To obtain a more complete understanding of the persisting gender earnings gap in Germany, this paper investigates both the cross-sectional and biographical dimension of gender inequalities. Using an Oaxaca Blinder decomposition, we show that the gender gap in annual earnings is largely driven by women's lower work experience and intensive margin of labor supply. Based on a dynamic microsimulation model, we then estimate how gender differences accumulate over work lives to account for the biographical dimension of the gender gap. We observe an average gender lifetime earnings gap of 51.5 percent for birth cohorts 1964-1972. We show that this unadjusted gender lifetime earnings gap increases strongly with the number of children, ranging from 17.8 percent for childless women to 68.0 percent for women with three or more children. However, using a counterfactual analysis we find that the adjusted gender lifetime earnings gap of 10 percent differs only slightly by women's family background.
urn:nbn:de:kobv:188-refubium-34038-1
Keywords: D31; J13; J16; J31; 330; Lifetime Earnings; Gender Inequality; Parenthood; Dynamic Microsimulation